Preferences For Childbirth At Primary Health Care And Hospitals Of Pregnant Women At The Tanah Abang And Kemayoran Primary Health Care - Windhi Kresnawati; Helena Angelica; Kevin Kristian; Dwirani Amelia; Elida ‎ (JOURNAL EDUCATIONAL OF NURSING(JEN), 2026)
The 2023 Indonesia Health Survey reported that 60.7% of deliveries in Jakarta occurred in hospitals, while only 14.2% took place in primary health care (puskesmas), indicating a gap between antenatal care (ANC) utilization and delivery services at puskesmas despite high ANC attendance. This qualitative exploratory study was conducted at Tanah Abang and Kemayoran Primary Health Care from July to October 2025, involving 114 respondents in focus group discussions, with data analyzed using thematic analysis, triangulation, and inter-rater agreement. The findings identified six major themes related to ANC and delivery place selection, influencing factors, perceptions of puskesmas services, and maternal health education. Distance and accessibility were the main reasons for choosing puskesmas for ANC, while hospitals were preferred for delivery due to perceived higher safety, availability of specialists, and more complete facilities, particularly for high-risk pregnancies. Utilization of maternal health services was strongly supported by the BPJS/JKN program, as well as family support, prior delivery experiences, and socioeconomic factors. Although puskesmas services were generally perceived positively, gaps were identified in lactation counseling and antenatal class implementation, indicating the need to strengthen health education and provider communication to enhance trust and utilization of puskesmas delivery services.